The attitudes to inclusion and Teacher Efficacy for Inclusive Practices scales: psychometric properties across Swiss in-service, pre-service, and special education teachers - Wüthrich, Sergej; Sahli Lozano, Caroline (Frontiers in Psychology, 2025)
IntroductionThis study examined the psychometric properties of two widely used scales measuring teacher attitudes (Attitudes to Inclusion Scale; AIS) and self-efficacy (Teacher Efficacy for Inclusive Practices Scale; TEIP and its short form TEIP-SF) toward inclusive education.MethodsUsing a sample of Swiss teachers (N = 1,546), including pre-service regular teachers (n = 147), in-service regular teachers (n = 1,168), and special education teachers (n = 231), we applied confirmatory factor analysis (CFA) and exploratory structural equation modeling (ESEM) to assess factor structure and assessed reliability, convergent validity and discriminant validity of the scales.ResultsResults indicated that ESEM models outperformed CFA models. While the AIS and TEIP-SF demonstrated strong psychometric properties across all evaluation criteria, the TEIP showed limitations in convergent and discriminant validity, particularly in its collaboration factor. Alignment procedures demonstrated approximate measurement invariance of all scales across teacher groups. Latent mean comparisons revealed that special education teachers reported significantly more positive attitudes (d = 0.74–0.88) and higher self-efficacy in instruction (d = 0.69–0.72) and collaboration (d = 0.74–0.78) compared to in-service regular teachers. Pre-service teachers also showed more positive beliefs (d = 0.44) but lower self-efficacy in behavior management (d = 0.22–0.25) than in-service teachers.DiscussionThe findings support the use of the AIS and TEIP-SF for assessing attitudes and self-efficacy toward inclusion across different teacher groups and support domain-specificity of teacher self-efficacy.